The Political Economy of Fostering a Wood-based Bioeconomy in Germany - Nadine Pannicke; Erik Gawel; Nina Hagemann; Alexandra Purkus; Sebastian Strunz (German Journal of Agricultural Economics (GJAE), 2015)
To increase the sustainability of economic processes and products as well as the use of sustainable resource inputs, a transition is required from the hitherto predominantly fossil resource-based "throughput economy" towards a circular flow economy based on renewable resources, the so-called bioeconomy. This paper considers the transition challenge from the perspective of dynamic theories on lock-in effects and lock-out options. Within this framework, a successful transition requires a twofold equilibrium: the economic sustainability equilibrium and a corresponding political equilibrium providing the corresponding transition policies. Based on the positive analysis of both current bioeconomy policies and policy demand by bioeconomy actors in Germany, this paper devel-ops recommendations on how a political equilibrium may be achieved which favors a sustainability-oriented transformation to a bioeconomy. One means of doing so, for example, is to combine a gradual development of existing policies with efforts to identify and support innovative niche products and processes.
Keywords: 330